Interaction between different forms of proximity in inter‐organizational scientific collaboration: The case of medical sciences research network in the Yangtze River Delta region. Issue 5 (29th March 2019) - Cao, Zhan; Derudder, Ben; Peng, Zhenwei
Abstract: The combined importance of geographical and non‐geographical proximity has been extensively examined, but the interactions between both—substitution/complementarity—are less well understood. This paper therefore explores the impact of, and interaction between different forms of proximity (geographical, institutional, social, cognitive and cultural/linguistic proximity) on knowledge collaboration in the medical sciences sector in the Yangtze River Delta. The results show that most dimensions of proximity have a positive impact on scientific collaboration. We find that institutional proximity can compensate for the lack of geographical proximity, which in turn reinforces social and cognitive proximity in facilitating inter‐organizational scientific collaboration. Resumen: La importancia combinada de la proximidad geográfica y no geográfica ha sido ampliamente examinada, pero las interacciones entre ambas ‐sustitución/complementariedad‐ son menos conocidas. Por lo tanto, este artículo examina el impacto de las diferentes formas de proximidad (geográfica, institucional, social, cognitiva y cultural/lingüística), y su interacción, en la colaboración en materia de conocimiento en el sector de las ciencias médicas en el delta del río Yangtze. Los resultados muestran que la mayoría de las dimensiones de la proximidad tienen un impacto positivo en la colaboración científica. Se encontró que la proximidad institucional puede compensar la falta de proximidad geográfica, lo que a su vez refuerza la proximidad social y cognitiva al facilitar la colaboración científica entre organizaciones. 抄録: これまで、地理的近接性と非地理的近接性の統合した重要性に関しては広く検討されてきたが、これら両者間の相互作用、すなわち代替性/相互補完性については、前者ほどには解明されていない。そこで本稿では、長江デルタにおける医療科学セクターの知識コラボレーションに対する、形態の異なる近接性(地理的、制度的、社会的、認知的、文化/言語的)の影響およびそれらの間の相互作用を検討する。結果から、近接性のほとんどの形態は科学的コラボレーションに正の影響を与えていることが示される。制度的近接性は、地理的近接性の欠如を補完し、さらには組織間の科学コラボレーションを促進する上で、社会的近接性と認知的近接性を補強するという知見が得られた。